Application of shaped tube as preform to eliminate the forming defects of ribbed tube in multi-pass drawing. (28th April 2023) - Li, Wei; Liu, Shengqiang; Feng, Pengni; Wang, Jiapeng; Zhou, Jing; Wang, Baoyu
Abstract: Thin-walled ribbed tube with small-diameter is a newly designed structure, which is used in nuclear fuel cladding. Due to the high precision requirements of nuclear industry applications, the integral forming and precision forming of ribbed tube are the focus of research. However, the forming defects — rib grooves often fail to achieve the precision forming of ribbed tube. Therefore, the two-pass drawing process is designed to realize the integral forming of ribbed tube and the forming mechanism of ribbed tube is analyzed. Further, the effect of round tube as billet on the forming accuracy of ribbed tube is studied. The results show that the rib groove defects are caused by local large deformation and excessive metal flow, which can not be completely eliminated only by changing the billet size of round tube. Based on this, three kinds of shaped tubes as preforms instead of round billet are proposed for eliminating the rib groove defects to realize the precision forming of ribbed tube. The effects of different preform schemes on the forming accuracy, drawing force and stress distribution of ribbed tube are compared and discussed. By selecting the optimal preform scheme and applying it to multi-pass drawing, the completely defect-free ribbed tube is obtained. At the same time, after adopting the appropriate billet size, the rib filling fullness of the tube is further improved and closer to the target size. Moreover, the microstructure of ribbed tube after multi-pass drawing are observed. The martensite and deformation twins appeared due to work hardening and the grain size refinement degree of different positions are different due to different deformation degree.